The Effect of Exercise and Melatonin on Social Isolation Stress-Induced BDNF Downregulation and Neurogenesis - Musuroglu, Seval Keloglan; Sahin, Leyla; Annac, Ebru; Tirasci, Nurhan (Springernature, 2025)
ObjectivesExercise and melatonin have effects on the cognitive functions of the brain in situations such as stress. Although combined exercise and melatonin may have synergistic effects on various neurodegenerative disorders, their effects on stress are not fully understood. Our study aimed to investigate the combination of treadmill exercise and melatonin on neuronal changes induced by social isolation (SI) stress.Materials and MethodsIn this study, 4-month-old Wistar albino male rats (n = 30) were divided into 5 groups: control (C); social isolation (SI); SI + exercise (SIE); SI + melatonin (SIM); and SI + exercise + melatonin (SIEM). During the last two weeks of 6-week social isolation stress, experimental animals were exercise training and administered melatonin treatment. Following was investigated serum corticosterone, hippocampal BDNF, GFAP, and SNAP-25 gene expression levels and neurogenesis in the dentate gyrus.ResultsBDNF was found to be down regulated in the SI (p = 0.010) and SIE group (p = 0.007) compared to the C group, but this down regulation was reversed with melatonin treatment. Pyknotic cells and increased anti-caspase 3 cells were observed in the SI group. Furthermore, increased mitotic activity was more pronounced in the SIM group than SIE group.ConclusionThe present study shows that a combination of treadmill exercise and melatonin does not have a more significant effect on SI stress than either treatment alone, but both treatments increase neurogenesis. In future studies, we suggest investigating different durations and types of exercise and melatonin treatment combinations to better understand the hippocampal mechanisms induced by SI.
Keywords: Social isolation; Treadmill exercise; Melatonin; Hippocampus; Neurogenesis